KOMUNIKASI PENDIDIKAN ISLAM DALAM MENINGKATKAN HARMONISASI HUBUNGAN KEPALA SEKOLAH, GURU, DAN SISWA - Rozali, M.; Tanjung, Lidra Agustina; Kharomah, Larasati Nur (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to examine the role of communication in Islamic education, focusing on Baitul Qur’an Binjai. The main problem arose from poor communication between the principal and former teachers, which created conflict, decreased student motivation, and reduced parental trust. The research applied a descriptive qualitative approach using observation, interviews, and documentation. Findings revealed that after the teacher replacement, internal communication became more harmonious, principals and teachers supported each other, and students developed closer interactions with educators. The learning environment grew more conducive, innovations emerged, and parents’ trust significantly improved. These results highlight that Islamic communication—open, dialogical, and based on Qur’anic values—plays a strategic role in fostering harmony, enhancing learning quality, and strengthening the school’s image as a progressive Islamic educational institution.